Low Metal Loading Palladium Mixed-Oxides Catalyst for the Synthesis of Glycerol Carbonate - Anisah Sajidah, Haji Saud; Indran, Vidhyaa Paroo; Nazira, Mahmud; Mohd Hasbi, Ab. Rahim (Asian Online Journals, 2016)
Glycerol carbonate can be readily synthesized from glycerol and urea catalyzed by PdZnO, PdSnO2, SnO2, and ZnO. The superior catalytic activity of ZnO over SnO2 is mainly due to basicity property. The incorporation of low metal loading of Pd on both SnO2 and ZnO produced higher yield of glycerol carbonate to bulk material counterpart. In addition, the sol-gel technique was shown to have higher turn-over frequency (TOF) due to highly disperse Pd with small crystallite size.